Symbolic meanings, landowner support, and dedicated bioenergy crops in the rural northeastern United States. (June 2019) - Eaton, Weston M.; Burnham, Morey; Running, Katrina; Hinrichs, C. Clare; Selfa, Theresa
Highlights: Tests whether symbolic fit corresponds with support for renewable energy technologies. Conceptualizes meanings for land and landscapes as place-based meanings. Finds meanings for land and technology correspond with support for dedicated bioenergy crops. Shows different meaning combinations underpin bioenergy support. Abstract: Recent research on social acceptance of large-scale renewable energy systems development has turned from an earlier focus on social opposition, such as Not In My Backyard (NIMBY) stances, toward assessing the 'symbolic fit' between meanings for place and proposed technology development that people near development sites hold. This quantitative study extends the symbolic fit hypothesis by testing how varied combinations of meanings for place and technology influence Northeast U.S. rural landowners' support for dedicated bioenergy crop production in their communities. Drawing on a survey of 907 landowners who have ten or more acres of land suitable for perennial bioenergy crops, we tested ten combinations of symbolic meanings regarding bioenergy crop technologies and land as place. We found that when combined with either protectionist or utilitarian meanings for one's land, viewing bioenergy crop production as an innovative way to address environmental challenges increased the likelihood of support for local development of bioenergy crops. Similarly, different symbolic meanings regarding one's land combined with seeing little community benefit from bioenergy crops reduced the likelihood of support. Given the important role of private landowners in many regions of Western nations considering bioenergy development, the symbolic meanings held by landowners merit attention. By recognizing the complex, conjunctural sources of meanings that inform landowners' propensities to support new renewable energy project development, new and emerging energy projects can incorporate more polyvalent views into design and implementation and approach public engagement opportunities accordingly.